229k views
5 votes
Solve the following by using mathematical Induction. For >/ 1

1^2+2^2+3^3+......+ n^2 = 1/6 n(n+1)(2n+[)

User MarkCo
by
5.1k points

1 Answer

4 votes

Answer:

See explanation

Explanation:

Prove that


1^2+2^2+3^3+...+n^2=(1)/(6)n(n+1)(2n+1)

1. When
n=1, we have

  • in left part
    1^2=1;
  • in right part
    (1)/(6)\cdot 1\cdot (1+1)\cdot (2\cdot 1+1)=(1)/(6)\cdot 1\cdot 2\cdot 3=1.

2. Assume that for all
k following equality is true


1^2+2^2+3^3+...+k^2=(1)/(6)k(k+1)(2k+1)

3. Prove that for
k+1 the following equality is true too.


1^2+2^2+3^3+...+(k+1)^2=(1)/(6)(k+1)((k+1)+1)(2(k+1)+1)

Consider left part:


1^2+2^2+3^2+...+(k+1)^2=\\ \\=(1^2+2^2+3^3+...+k^2)+(k+1)^2=\\ \\=(1)/(6)k(k+1)(2k+1)+(k+1)^2=\\ \\=(k+1)\left((1)/(6)k(2k+1)+k+1\right)=\\ \\=(k+1)(2k^2+k+6k+6)/(6)=\\ \\=(k+1)(2k^2+7k+6)/(6)=\\ \\=(k+1)(2k^2+4k+3k+6)/(6)=\\ \\=(k+1)(2k(k+2)+3(k+2))/(6)=\\ \\=(k+1)((k+2)(2k+3))/(6)

Consider right part:


(1)/(6)(k+1)((k+1)+1)(2(k+1)+1)=\\ \\(1)/(6)(k+1)(k+2)(2k+3)

We get the same left and right parts, so the equality is true for
k+1.

By mathematical induction, this equality is true for all n.

User Sergey Barskiy
by
4.9k points